Protein crowding and lipid complexity influence the nanoscale dynamic organization of ion channels in cell membranes. Issue 1 (December 2017) - Duncan, Anna; Reddy, Tyler; Koldsø, Heidi; Hélie, Jean; Fowler, Philip; Chavent, Matthieu; Sansom, Mark
Abstract Cell membranes are crowded and complex environments. To investigate the effect of protein-lipid interactions on dynamic organization in mammalian cell membranes, we have performed coarse-grained molecular dynamics simulations containing >100 copies of an inwardly rectifying potassium (Kir) channel which forms specific interactions with the regulatory lipid phosphatidylinositol 4, 5-bisphosphate (PIP2 ). The tendency of protein molecules to cluster has the effect of organizing the membrane into dynamic compartments. At the same time, the diversity of lipids present has a marked effect on the clustering behavior of ion channels. Sub-diffusion of proteins and lipids is observed. Protein crowding alters the sub-diffusive behavior of proteins and lipids such as PIP2 which interact tightly with Kir channels. Protein crowding also affects bilayer properties, such as membrane undulations and bending rigidity, in a PIP2 -dependent manner. This interplay between the diffusion and the dynamic organization of Kir channels may have important implications for channel function.